Examining non-medical prescribing trends in New Zealand: 2016-2020 - Rakhee Raghunandan; Carlo A. Marra; June Tordoff; Alesha Smith (BMC, 2021)
Abstract Background Population growth and general practitioner workforce constraints are creating increasing demand for health services in New Zealand (NZ) and internationally. Non-medical prescribing (NMP) is one strategy that has been introduced to help manage this. Little is known about the NMP practice trends in NZ. The aim of this study was to provide a current overview of the scale, scope, and trends of NMP practice in NZ. Methods All claims for community dispensed medicines prescribed by a non-medical prescriber were extracted from the NZ Pharmaceutical Collection for the period 2016-2020. Patient demographics were retrieved from the Primary Health Organisation enrolment collection. These national databases contain prescription information for all subsidised community pharmacy medicines dispensed and healthcare enrolment data for 96% of New Zealanders. Results The proportion of prescriptions written by all NMP providers and patients receiving NMP prescriptions increased each year from 1.8% (2016) to 3.6% (2019) and 8.4% (2016) to 14.4% (2019) respectively. From 2016 to 2019, the proportion of NMP patients who had at least one NMP prescription increased from 26% to 39% for nurse prescribers, from 1% to 9% for pharmacist prescribers, from 2% to 3% for dietitian prescribers, and decreased from 47% to 22% for dentists, and from 20% to 12% for midwives. The most commonly prescribed medicines were antibiotics (amoxicillin, amoxicillin with clavulanic acid, and metronidazole), and analgesics (paracetamol, and codeine phosphate). While some NMP providers were prescribing for patients with greater health needs, all NMP providers could be better utilised to reach more of these patients. Conclusions This study highlights that although the NMP service has been implemented in NZ, it has yet to become mainstream healthcare practice. This work provides a baseline to evaluate the NMP service moving forward and enable policy development. Improved implementation and integration of primary care NMP services can ensure continued access to prescribing services and medicines for our communities.